Ouvidorias em saúde : proposta de um modelo de avaliação de sua institucionalização enquanto instrumento de accountability e gestão estratégica e participativa - Nabas, João Madeira (2016)
The democratization process in Brazil that led to the enactment of the Federal Constitution of 1988 paved the way for the emergence of various mechanisms for participation and social control, among which stand out in this work, public ombudsmen. Taking into account that public ombudsmen are democratic spaces for participation and instruments of strategic management, in that mediate between citizens and administration and, on the assumption that the constituent elements of the institutionalization of these areas impact the results, this work intends to propose an evaluation model the degree of institutionalization of ombudsmen - specifically the health ombudsman - to identify which variables influence positively or negatively to its consolidation as a forum for participation and accountability tool, both within the state bureaucracy as in society. For this, this paper makes a conceptual review and story about the public ombudsman institute; examines its role and conceptualization, while accountability mechanism and creates a diagnostic tool to measure the rate and level of institutionalization of public ombudsmen in health, based on legal instruments governing their operation.